Pengaruh Formulasi Tepung Rumput Laut (Echeuma Cottonii) Dan Tepung Maizena Terhadap Sifat Kimia Sosis Ikan Tongkol (Euthynnus Affinis) - Hardiana, Windi Amalia; Nugroho, Matheus (Fishery Product Technology Study Program, Yudharta University, Pasuruan, 2022)
Generally, sausages are made from beef, chicken meat, and pork. But now fish sausages have been developed, which are sausages made from fish meat. Research has been conducted that aims to determine the effect of seaweed flour formulations on the chemical properties of cob fish sausages (Euthynnus affinis) and find out the best treatment formulations. The method used in this study is quantitatively experimental and uses a Complete randomized design (RAL) with 2 treatment factors The treatment applied is the formulation of Cob Fish 200 g: Seaweed Flour 10 g: Cornstarch 45 g. Cob Fish 200 g: Seaweed Flour 25 g: Cornstarch 35 g. Cob Fish 200 g: Seaweed Flour 35 g: Cornstarch 20 g. Cob Fish 200 g: Seaweed Flour 40 g: Cornstarch 15 g. Cob Fish 200 g: Seaweed Flour 50 g: Cornstarch 5 g. The results of the cob fish sausage product were tested by water content analysis, and protein content All data were analyzed using the Homogeneity Test and then continued with the Normality and ANOVA tests. The results of the study showed that the formulation of seaweed flour and cornstarch was a significant effect on the chemical properties of cob fish sausages. The proportion of seaweed flour and cornstarch received by the panelists were (Cob Fish 200 g: Seaweed Flour 50 g: Cornstarch 5 g).